PEMAHAMAN YANG BIAS GENDER - Agustin Hanafi (Takammul : Jurnal Studi Gender dan Islam Serta Perlindungan Anak, 2017)
Understanding verses and hadiths that gender bias, often used as a legitimation for inequality relationships women and men. Forexample, the interpretation of the word nafs wahidah that could be interpreted as Adam or also of the same material with Adam. However, the important thing is, that it does not mean there are more superior than others. Understanding verses and hadiths that gender bias is also found in understanding the hadith about the creation of woman from the rib. The creation of woman from the rib here is not in the true meaning, but often harfiyah interpreted giving rise to the perception that women in Islam is a second being. This understanding arises because of an incomplete understanding of the meaning of the verse and the hadith, and also due to the only partial understanding.